Tolerance of Macrophytes and Grasses to Sodium and Chemical Oxygen Demand in Winery Wastewater - Zingelwa, N.S.; Wooldridge, J. (South African Journal of Enology and Viticulture, 2016)
Winery wastewater often contains elevated concentrations of sodium (Na), and has a high chemical oxygen demand (COD). In constructed wetlands, Na may be removed through phytoremediation by such macrophytic plants as Typha latifolia, Juncus acutus and Scirpus maritimus. The relative abilities of these plants to absorb Na, and to tolerate high COD wastewaters was determined in a glasshouse pot trial. Also tested were Pennisetum clandestinum (Kikuyu) and Vetiveria zizanioides (Vetiver) grass, which are used on wastewater disposal sites. Treatments consisted of factorial combinations of Na and COD. Toxicity symptoms were not apparent below 16.2 μM Na/L < 5 000 mg COD L, but were marked at ≥ 40 μM Na/L and ≥ 15 000 mg COD/L. Of the macrophytes, J. acutus was the least affected by high Na and COD levels. Averaged across the Na and COD treatments, total plant dry mass (DM) in the macrophytes peaked at 40 μM Na/L, as did ability to tolerate COD. The total Na in the top growth was greatest in J. acutus from which 61.4 mg Na/plant (767 mg/m2) could potentially be harvested after six months. Equivalent figures for T. latifolia and S. maritimus were 38.8 and 25.0 g/plant, respectively. Of the grasses, P. clandestinum produced 35% more total DM than V. zizanioides. Top-growth Na contents were, respectively, 1427 and 29.1 mg/ plant. To maximise Na uptake in harvestable plant components, J. acutus should be planted in wetlands, and P. clandestinum in pastures used for wastewater disposal.